Improving Students Activity and Students Mathematic Learning Outcomes by Using Constructivism Learning Approach - Sholahudin Al Ayubi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to describe the activities and student learning outcomes by using konstruktivism approach. To find whether or not improving of students activity by using konstruktivism approach. To find whether or not improving of students learning outcomes by using konstruktivism approach The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII at SMP Ainul Yaqin. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords:konstruktivisme, students activity, and mathematical learning outcomes